A epistemologia da ciência segundo Thomas S. Kuhn - PASSOS, Dirceu Rodrigues dos (2023)
In the Kuhnian conception, science develops through episodes that test different modes or qualities of research. These episodes are cyclical and alternate throughout the history of scientific development. According to this point of view, science cannot be cumulative or linear; on the contrary, its development is discontinuous and marked by scientific revolutions. The set of ideas presented in the works of Thomas Samuel Kuhn on the development of scientific knowledge contributed to a better understanding of science as a historical and social construction of a scientific community. Kuhn proposed the notion of “scientific revolution” to explain how new scientific theories arise and replace old ones. He argued that the development of scientific knowledge does not occur in a linear fashion, but in leaps or “revolutions”. This occurs when a new scientific theory (“paradigm”) is accepted by the scientific community, allowing a significant leap in scientific knowledge in an area. Paradigms establish patterns of reasoning, methods and basic principles for carrying out scientific research. From this perspective, this paper investigates Thomas Kuhn’s conception of scientific development, which can be taken from his book The Structure of Scientific Revolutions. In this regard, we try to introduce pre-Kuhnian concepts and try to explain terms used by Kuhn in his book, such as historical interpretation of science, paradigms, normal and extraordinary science, and scientific revolutions and their solutions, as well as their implications for modern science.